L-Aminoguanidine Induces Imbalance of ROS/RNS Homeostasis and Polyamine Catabolism of Tomato Roots after Short-Term Salt Exposure - Ágnes Szepesi; László Bakacsy; Attila Fehér; Henrietta Kovács; Péter Pálfi; Péter Poór; Réka Szőllősi; Orsolya Kinga Gondor; Tibor Janda; Gabriella Szalai; Christian Lindermayr; László Szabados; et al. (MDPI AG, 2023)
Polyamine (PA) catabolism mediated by amine oxidases is an important process involved in fine-tuning PA homeostasis and related mechanisms during salt stress. The significance of these amine oxidases in short-term responses to salt stress is, however, not well understood. In the present study, the effects of L-aminoguanidine (AG) on tomato roots treated with short-term salt stress induced by NaCl were studied. AG is usually used as a copper amine oxidase (CuAO or DAO) inhibitor. In our study, other alterations of PA catabolism, such as reduced polyamine oxidase (PAO), were also observed in AG-treated plants. Salt stress led to an increase in the reactive oxygen and nitrogen species in tomato root apices, evidenced by in situ fluorescent staining and an increase in free PA levels. Such alterations were alleviated by AG treatment, showing the possible antioxidant effect of AG in tomato roots exposed to salt stress. PA catabolic enzyme activities decreased, while the imbalance of hydrogen peroxide (H2O2), nitric oxide (NO), and hydrogen sulfide (H2S) concentrations displayed a dependence on stress intensity. These changes suggest that AG-mediated inhibition could dramatically rearrange PA catabolism and related reactive species backgrounds, especially the NO-related mechanisms. More studies are, however, needed to decipher the precise mode of action of AG in plants exposed to stress treatments.